Sundanese Perceptions and Preferences Towards Lalaban Menu: an Ethnoscience Study in Learning - Maryanti, Sri; Sriyati, Siti; Liliawati, Winny (Chemistry Education Department, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga, 2024)
Lalapan, a typical Sundanese side dish, has cultural significance and high nutritional value for its people. The purpose of the study was to gain insight into how Sundanese people perceive and like the lalaban menu, the traditional menu in their culture as well as their preferences in terms of taste and presentation. This study, reveals the meaning and cultural values inherent in the lalaban menu in Sundanese culture, as well as identifying specific elements of the lalaban menu by scientific principles. This study will also analyze the needs of students in science learning in junior high schools and use these findings as a basis for designing ethnoscience-based learning models that incorporate Sundanese local wisdom around the lalaban menu. This research is expected to help improve understanding of the meaning and value of Balaban culture in Sundanese culture. The research method is an explorative survey with observation techniques through the dissemination of questionnaires with an ethnoscientific approach. Data were collected through observation of 350 participants from 10 cities/districts. The data obtained were analyzed descriptively. The results showed that Balaban was already known to the public, lalapan has a taboo that people believe as a myth. However, there is a scientific explanation from the perspective of ethnoscience, fresh vegetables are important and consumed not just for cultural heritage but there are benefits that can be obtained, types of fruits, vegetables, or plants that are used as potential fresh vegetables that can be consumed, nutritional studies of fresh vegetables, characteristics or inventory of plants used as fresh vegetables, have symbolic meaning as balance, simplicity, and closeness to nature. Other perceptions of tehadap fresh vegetables according to surveys that have been conducted variously. Preference for fresh vegetables is influenced by taste, texture, and nutritional value. In conclusion, the perception and preference of lalaban are not only based on taste and texture but also influenced by cultural significance and nutritional value.